Chromosomal integration of plasmid DNA by homologous recombination in Enterococcus faecalis and Lactococcus lactis subsp. lactis hosts harboring Tn919. - Casey, J (1991)
Integration of pCI192, a pBR322-derived vector plasmid containing homology to the chromosomally located conjugative transposon Tn919 was observed in two strains that harbor Tn919, namely, Enterococcus faecalis GF590 and Lactococcus lactis subsp. lactis CH919. Hybridization analysis indicated that single-copy integration of the plasmid had occurred at low frequency. The Tn919::plasmid structure was conjugated from an E. faecalis donor to a L. lactis recipient, although at lower frequencies than was Tn919. Segregation of the tetracycline and chloramphenicol resistance markers during conjugation was observed. The integration strategy described allows for DNA manipulations to be performed in an easily manipulated model host strain with the subsequent transfer of integrated structures by conjugation to any strain capable of receiving Tn919. The results indicate that homologous recombination events may be used to introduce plasmid-encoded genes to the lactococcal chromosome.